GANGGUAN SPERMATOGENESIS SETELAH PEMBERIAN MONOSODIUM GLUTAMAT PADA MENCIT (MUS MUSCULUS L.) - SUKMANINGSIH, A.A.SG.A; ERMAYANTI, I GUSTI AYU MANIK; WIRATMINI, NGURAH INTAN; SUDATRI , NI WAYAN (Jurnal Biologi Udayana; Vol 15 No 2 (2011): Jurnal Biologi, 2011)
This study was conducted to investigate the effect of monosodium glutamate (MSG) on spermatogenesis of male experimental mice.using 32 twelve-week old mice. They were divided randomly into 4 groups, each group consisted of 8 mice. One group was used as control, three groups were used as treatment, which received 1.5 mg/g body weight/day, 3 mg/g body weight/day and 4.5 mg/g body weight/day of MSG solution in destilled water for 35 days. The result showed that MSG treatment led to disturbance on spermatogenesis by reduction in some of the parameter studied. There was a significant (p 0.05).
Keywords: MSG; Mus musculus L.; Spermatogenesis